SPANISH CUISINE: AWARENESS, PREVALENCE, AND SATISFACTION FROM THE PERSPECTIVE OF HOSPITALITY EMPLOYEES - Ivanović, Velibor; Čugalj, Milana; Kalenjuk Pivarski, Bojana; Šmugović, Stefan (The Business of Tourism, 2025)
Spanish cuisine represents one of the most significant gastronomic traditions, known for its diversity, regional specialties, and cultural value. Its variety of culinary products has developed as a result of Spain’s unique geographical position and complex cultural and historical influences. The cuisine of this country has long transcended its borders and is now considered one of the most important international cuisines, with numerous dishes embraced worldwide. The subject of this research is the awareness and presence of Spanish cuisine, as well as the satisfaction with its offering in hospitality establishments in Belgrade, a major hospitality and tourism center. The primary objective is to examine the level of knowledge among hospitality workers regarding the characteristics of Spanish gastronomy and to determine the representation of Spanish dishes in the current food service offerings. The aim of the research is to assess the extent to which hospitality employees are familiar with the characteristics of Spanish cuisine, how present these dishes are in menus, and whether there is satisfaction with or potential for their broader inclusion in the offer. The research was conducted through a survey of employees in hospitality establishments in the Belgrade area, and the data were analyzed using descriptive statistics. The results of the study indicated limited awareness of Spanish cuisine, low representation of its dishes in the current offering, but also a high openness toward incorporating them into menus.